Pengaruh Desain Interior Mencusuar Cafe & Resto Dago Terhadap Pengalaman Wisatawan - Aldi Yusna Jatnika; Chintia Restiana (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This study was conducted to determine the interior design at Mencusuar Cafe &; Resto Dago, the influence of restaurant interior design on guest experience and satisfaction at Mencusuar Cafe &; Resto Dago. Some of the analysis methods used are descriptive methods. The problem in this study is in changing priorities to design and promote various types of café spaces, from those that were originally oriented to the physical and physiological comfort of users, now starting to prioritize the beauty and visual uniqueness of the space in order to become an 'instagrammable' selfie tourist destination. Therefore, this study aims to see in detail the role of interior design on Mencusuar Café &; resto Dago and also on people's consumption patterns. The theory used is the theory of interior design, a design of building space to accommodate and the needs of tourists to feel comfortable and safe. The results of this study can conclude that Mencusuar café & resto Dago in addition to attracting the building, instagrammable photo spots, many facilities exist and can be used by tourists. That the elements of Mencusuar café & resto Dago that have an influence on the level of consumer satisfaction are physical environmental factors such as furniture, lighting, color combinations, interior decoration, sound, temperature, good coffee quality affect the pleasant aroma of the coffee shop. Researchers hope this study can provide inspiration for tourists who want to visit to get information first. Make the experience valuable for visitors.